HARDWARE IMPLEMENTATION OF FUZZY MAXIMUM POWER POINT TRACKING THROUGH SLIDING MODE CURRENT CONTROL FOR PHOTOVOLTAIC SYSTEMS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
This paper deals with an intelligent-robust control method for maximum power point tracking (MPPT) of photovoltaic (PV) system under irradiation conditions change. The proposed MPPT scheme incorporates an intelligent fuzzy controller with a robust sliding mode current controller to enhance the MPP pursuit performance (speed and accuracy tracking, steady state power oscillations). To prove the performance improvement of the proposed scheme, a comparison is performed experimentally with both conventional IncCon algorithm and conventional incremental through sliding mode current control under different irradiance levels. The results obtained through the developed prototype based on dSPACE DS1104 board demonstrate that this method provides better performance and more robustness to the MPPT in terms of power oscillations, convergence speed to the optimal point and accuracy tracking following irradiation changes.
Keywords: Photovoltaic energy; Maximum power point tracking (MPPT); Fuzzy logic maximum power point (Fuzzy MPPT); Sliding mode current controller (SMCC)